Management of fungal plant pathogens (CABI, 2010)
This book provides an overview of our current knowledge of some plant-pathogen interactions in economically important crops, emphasizing the importance of pathogenic fungi on fruits, cereals, postharvest crops and the establishment of plant diseases and drawing together fundamental new information on their management strategies based on conventional and eco-friendly methods, with an emphasis on the use of microorganisms and various biotechnological aspects of agriculture, which could lead to sustainability in modern agriculture. The book examines the role of microbes in growth promotion, as bioprotectors and bioremediators, and presents practical strategies for using microbes in sustainable agriculture. In addition, the use of botanicals vis-a-vis chemical pesticides is also reviewed. Contributions on new research fields such as mycorrhizas and endophytes are included. The book also examines in different chapters host-pathogen interactions in the light of the new tools and techniques of molecular biology and genetics.